2021
DOI: 10.1002/mds.28498
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Significantly Associated With Disease Severity in Spinocerebellar Ataxia Type 2 Patients

Abstract: A BS TRACT: Background: Spinocerebellar ataxia type 2 is a progressive neurodegenerative disorder due to an unstable expansion of a CAG repeat in the ATXN2 gene. Although weight loss has been associated with disease progression in several neurodegenerative conditions, it has been barely assessed in patients with spinocerebellar ataxia type 2. Objective: The objective of this study was to test whether body mass index is altered in patients with spinocerebellar ataxia type 2 with varying expansion sizes from ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
(189 reference statements)
2
2
0
Order By: Relevance
“…This study confirmed the negative association between CAG repeat length and BMI in SCA3 patients. This association has also been observed in other CAG repeat expansion disorders such as SCA2 and HD, 5,32,33 suggesting BMI as a disease biomarker shared by several polyglutamine diseases 32 . Extending a pioneering study showing a correlation between CAG repeat number and BMI in SCA3, 5 we provide further evidence that this association is partly mediated by tubular hypothalamic atrophy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study confirmed the negative association between CAG repeat length and BMI in SCA3 patients. This association has also been observed in other CAG repeat expansion disorders such as SCA2 and HD, 5,32,33 suggesting BMI as a disease biomarker shared by several polyglutamine diseases 32 . Extending a pioneering study showing a correlation between CAG repeat number and BMI in SCA3, 5 we provide further evidence that this association is partly mediated by tubular hypothalamic atrophy.…”
Section: Discussionsupporting
confidence: 80%
“…This association has also been observed in other CAG repeat expansion disorders such as SCA2 and HD, 5,32,33 suggesting BMI as a disease biomarker shared by several polyglutamine diseases. 32 Extending a pioneering study showing a correlation between CAG repeat number and BMI in SCA3, 5 we provide further evidence that this association is partly mediated by tubular hypothalamic atrophy. This mediation effect suggests that hypothalamic atrophy may be related to mutant ataxin-3 toxicity per se, the predominant pathology caused by CAG expansion.…”
Section: Discussionsupporting
confidence: 55%
“…A combination of clinical scales with quality-of-life measures, wearable sensors allowing free-living motor activity monitoring, neuroimaging biomarkers (MRI, MR spectroscopy, DTI) and fluid biomarkers (blood, CSF) is likely the best approach, not only to identify conversions from the asymptomatic stage to symptomatic condition, but also for the general monitoring of ataxias [37,38]. Pure clinical tools, such as the evaluation of the body mass index should not be excluded, as shown recently for BMI, which is significantly decreased in SCA2, with an association with age at onset and progression rate [39]. We may also have to re-consider how trials are designed in patients' registries of CAs given the major heterogeneity in clinical profiles and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson disease (PD) is a chronic neurodegenerative disease. The incidence of PD is closely related to population aging ( Almaguer-Mederos et al, 2021 ). With the aggravation of population aging in China, the incidence of PD is also increasing.…”
Section: Introductionmentioning
confidence: 99%